Polemics and Analysis of Critiism of IFRS by I. R. Sukharev and O. A. Sukhareva - RUSLAN S. Golovanov (Учёт. Анализ. Аудит, 2019)
The present article is to controvert the criticism in relation to International Financial Reporting Standards (IFRS). The purpose of the article is to contribute to the public discussion about the place of IFRS in the Russian financial accounting system. The article is divided into three parts: in the first part the author raises an issue of IFRS implementation in Russia. The second part is devoted to the importance of public debate of IFRS application and understanding in Russia. The author offers a very brief introduction to IFRS: key definitions and how to apply them. And the third part focuses directly on the IFRS weaknesses controversy. The emphasis here is made on the discussion of series of three articles by I. R. Sukharev and O. A. Sukhareva combined under the title “IFRS drawbacks”. The author does not agree with such a wording; he supports the uniformity of fundamentals and principles which result in comparability of financial statements worldwide. The article draws the attention to the previous negative experience and lack of modern strategic view that prevented the Russian professional accountancy community from creating up-to-date standards on their own